EVALUASI DAMPAK PROGRAM KAWASAN RUMAH PANGAN LESTARI KABUPATEN PACITAN - Noviyanto, Hendratmo (Master of Public Administration, Universitas Slamet Riyadi, 2021)
Food security at the household level has a very basic development perspective. This is due to access to food availability and balanced nutrition is a human right. The formation of quality human resources is greatly influenced by the success of meeting the adequacy of food needs and food security, so food is one of the strategic elements in economic development and national security. The study entitled